Effectiveness of Government Administration General Prayut Chan-o-cha among the 2019 Coronavirus Epidemic Crisis in Narathiwat Province - Rathachatranon, Wanlop; Chansilp, Vacharin (Rajapark Journal, 2023)
The objectives of this research were: 1. to study the level of political news perception and public opinion in Narathiwat Province; 2. to study the personal factors influencing people’s opinions in Narathiwat Province; and 3. to study the relationship between political news perception and people’s opinions in Narathiwat Province. to the effectiveness of the administration of the government of General Prayut Chan-o-cha. The sample consisted of 312 people, aged 15 and over, in Narathiwat Province. The instrument used to collect the data was a questionnaire. The statistics used in the data analysis were percentage, mean, standard deviation, multiple classification analysis, and canonical correlation analysis. The statistical significance level was set at.05. The results of the research revealed that 1) the overall perception of political news was moderate, with the most recognition coming from traditional media, followed by personal media and social media with the least. 2) The opinions of the people in Narathiwat on the effectiveness of the administration of General Prayut Chan-o-cha’s government in overall and in terms of aspects, namely: wealth performance; Sustainability and the security performance from the 2019 coronavirus pandemic is low. 3) From the hypothesis testing, it was found that the age of the samples influenced their opinions on the effectiveness of the government administration of General Prayut Chan-o-cha, while gender, educational level, monthly income, occupation, and religion had no influence. The perception of political news was related to opinions on the effectiveness of the administration of General Prayut Chan-o-cha’s government.